Branch retinal artery occlusion in a young healthy patient: Embolism as a rare cause - Jyoti Jain; Shashank Banait; Tanvi Banait (Wolters Kluwer Medknow Publications, 2020)
Branch retinal artery occlusion (BRAO) is an acute, painless, vision threatening, ocular emergency among people older than 60 years having cardiovascular disease. Here, we present a case of BRAO which occurred due to embolism as a rare etiology in an otherwise healthy young Asian male without any systemic or ocular disorders. The patient was treated as an ocular emergency with improved vision and retinal perfusion. The patient did not complain of recurrence of symptoms in the 3 months after the treatment.